Proximal tibial strains following unicompartmental knee arthroplasty (UKA) : a finite element study - Wu, Jiajun (2015)
Unicompartmental knee arthroplasty (UKA) is well known as an effective treatment for osteoarthritis in recent years. Many studies have proven that UKA is efficient and reliable. However, complications after UKA cannot be eliminated. Fracture of proximal tibial is one of the critical failures studied for many years without a proper solution. Such failure may be attributed by erroneous surgical techniques or improper patient selection. Understanding the cause of fracture may help the surgeon avoid mistakes during surgery as well as preselection of appropriate patient for this treatment. This project used finite element analysis to evaluate the stress distribution on the proximal tibial following UKA. A three-dimensional (3D) tibia bone model was created with computed tomography (CT) scan data obtained from a human knee. The 3D model was used to investigate the effect of resection angle and extended saw-cut at the L-cut region on the stress distribution of the proximal tibial. This study found that smaller angle of resection slope lowers the stresses on the proximal tibial and extended saw-cut dramatically increases the stress concentration at the web cut region. Further work may include validation of the finite element model using the same cadaveric bone as the experiment and the stress distribution during a gait cycle after UKA.